2019
DOI: 10.1021/acs.cgd.8b01712
|View full text |Cite
|
Sign up to set email alerts
|

One Molecule, Four Colors: Discovering the Polymorphs of a Thieno(bis)imide Oligomer

Abstract: The crystallization of 2,2′-(5,5′-(ethyne-1,2-diyl)bis-(thiophene-5,2-diyl))bis (5-hexyl-4H-thieno[2,3-c]pyrrole-4,6(5H)dione), hereafter NTA, in different solvents and/or conditions yielded the identification of five different polymorphs which are characterized by impressive differences in their photophysical behavior. Phase I, phase II, phase III, and phase IV are characterized by a yellow, green, red, and orange emission under illumination with 365 nm light. The crystal structures of phase II and III were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The utilization of polymorphic crystals with different crystal structures composed of the same compound may offer a means of creating this diversification. Generally, different structures provide distinct characteristics such as shapes and colors, , luminescence, ,, mechanical properties, ,, and mechanical motions. For instance, Mittapalli et al reported diverse thermomechanical effects among polymorphs of the dichloro derivative of N -salicylideneaniline: jumping (forms I and III) and exploding (form II) related to a sudden phase transition. Hao et al discovered bending in the opposite directions for forms I and II of trans -4-cyano-4′-oxethyazobenzene by photoisomerization.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of polymorphic crystals with different crystal structures composed of the same compound may offer a means of creating this diversification. Generally, different structures provide distinct characteristics such as shapes and colors, , luminescence, ,, mechanical properties, ,, and mechanical motions. For instance, Mittapalli et al reported diverse thermomechanical effects among polymorphs of the dichloro derivative of N -salicylideneaniline: jumping (forms I and III) and exploding (form II) related to a sudden phase transition. Hao et al discovered bending in the opposite directions for forms I and II of trans -4-cyano-4′-oxethyazobenzene by photoisomerization.…”
Section: Introductionmentioning
confidence: 99%
“…33 The polymorphs usually can be easily distinguished by the different crystal morphology and luminescence. 34 Although the mechanical properties are apparently very important for their application, they have not been explored yet.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, we have been researching thienopyrrolyldione end-capped oligothiophenes, for simplicity hereafter referred to as thienoimides (TI), which display ambipolar charge transport with major n-type behavior, and many are also electroluminescent. This combination of properties turns these materials into potential candidates for field-effect transistors (OFETs) , and single-layer ambipolar light-emitting transistor devices (OLETs). , The possibility for variations in the basic chemical structure provides access to a large variety of TI-based oligothiophenes which can be obtained by changing the length and shape of the alkyl chains, by modifying the number of thiophene rings, or by inserting different bridges between them. , It is noteworthy that most of these solids are obtained as different polymorphs, depending on the recrystallization conditions or the deposition procedure, but the polymorphism is also evident for different alkyl chain lengths, as it has been observed with odd- and even-number alkyl chains . The polymorphs usually can be easily distinguished by the different crystal morphology and luminescence . Although the mechanical properties are apparently very important for their application, they have not been explored yet.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, crystal phases of core-modified (NTE, NTA and NTI) 68 and terminal-modified (Cx-NT4N) 72 oligothiophene derivatives showed relevant transitions upon thermal heating. 73 While platelet-like crystals of NTE (Fig. 12a) were persistent till the melting point, rod-like crystals showed an irreversible change of the emission from red to orange (corresponding to the emission of platelet-like crystals) without variation of the morphology after the heating cycle ''room temperature (RT) -200 1C -RT''.…”
Section: Polymorph Control By Post-synthesis Physical Methodsmentioning
confidence: 99%